PENERAPAN DENDA TA'ZIR PADA PRODUK PEMBIAYAAN MIKRO DI BRI SYARIAH KCP KOPO - Hasanah, Meti; Arifin, Asep (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2019)
ABSTRACTBRI Syariah Bank Kopo Sub-Branch Office is a sharia financial institution that imposes sanctions on capable customers who delay payments in the form of a sum of money agreed upon at the time of the contract. The Bank will impose the fine calculated from the payment due until the date the payment is repaid. This sanction is based on the ta'zir principle, which aims to make the customer more disciplined in carrying out his obligations. Penalties obtained from customers are returned to the customer by accumulating the amount of the fine at the end of the financing.This study aims to find out, (1) to find out the process of giving Micro Financing in BRISyariah KCP Kopo, (2) to find out the application of ta'zir fines to Pembiayan Mikro products at BRI Syariah KCP Kopo, (3) to find out the suitability between the DSN No Fatwa .17 / DSN-MUI / IX (a) 2000 with ta'zir fines on Pembiayan Mikro products at BRI Syariah KCP Kopo. In this framework, financing is one of the main tasks of the bank, namely the provision of funding facilities to meet the needs of the parties who constitute the unit deficit. For customers who default, delaying payment after a fall will be subject to sanctions in the form of financial financial penalties, which are regulated in Fatwa DSN No.17 / DSN-MUI / IX / 2000 concerning sanctions for capable customers who delay payments. This study uses descriptive research methods, namely by collecting, studying, analyzing, and interpreting data that are related to the implementation of fines. The data obtained were interviewedwith one of the Micro Account Officer staff, and supported by literature studies. The results of this research process of the provision of microfinance is carried out step by step in accordance with the bank's rules, one of which is the bank's basic reference in assessing whether or not customers are eligible for financing through analysis of character, capacity, capital, condition, and collecteral. The application of fines at BRI Syariah KCP Kopo is imposed on customers who delay the Bank's payment will impose the fine calculated from the payment due until the date the payment is paid. This sanction is based on the ta'zir principle. Conformity Fatwa DSN-MUI No. 17 / DSN-MUI / IX / 2000 with the application of fines at BRI Syariah KCP Kopo there is a discrepancy in point 6